Holy bonsai wolves: Chihuahuas and the Paris Hilton syndrome. (January 2014) - Redmalm, David
This article examines the reasons for the Chihuahua breed's popularity in contemporary western society by looking at two sets of data: Chihuahua handbooks and The Simple Life show, starring Paris Hilton and her Chihuahua Tinkerbell. The article argues that the Chihuahua is a holy anomaly : a creature which can be used in myths and rituals to temporarily alleviate the tension-filled binary oppositions and stereotypes inherent in a particular culture, in order to celebrate and reinforce that culture's categories and social order. The Chihuahua – or the bonsai wolf – transcends two binary oppositions fundamental to contemporary westerners: subject/object and nature/culture. Although the Chihuahua challenges a number of related binary oppositions, it is generally dismissed as a matter for humor, low-brow entertainment or expressions of sentimentality, rendering ritual encounters with Chihuahuas harmless. The article concludes by asking: what would happen if humans actually started listening to what the Chihuahua is telling them?